Road Accidents, Alcohol, and Drugs: An Emergency Room Study in Florence, Italy. (September 2013) - Allamani, Allaman; Holder, Harold; Santarlasci, Veronica; Bardazzi, Gabriele; Voller, Fabio; Mari, Francesco; Bertol, Elisabetta; Orsini, Cristina; Pepe, Pasquale
This article describes the potential contribution of alcohol and illicit drugs to increased risk of road accidents in Italy. Blood and urine samples were taken from patients admitted to five Emergency Rooms (ER) in metropolitan Florence, Italy, due to road traffic accidents within 3 hours of the accident. Seven hundred and thirty-five patients were tested to determine if alcohol and illicit drugs (amphetamines, opiates, cocaine, methadone, and cannabis) were present in urine and blood. Approximately 22% of patients were positive for at least one substance at night-time (20:00 to 5:59), and 18% were positive on the weekends (20:00 Friday to 05:59 Monday). Almost 80% of all alcohol-positive patients had a blood-alcohol concentration (BAC) equal to or exceeding the legal limit. Findings indicated that alcohol and illicit drugs were important contributors to traffic accident risk and suggest prevention strategies for alcohol-related road accidents in Italy may need to follow those employed in other countries, including frequent and highly visible enforcement of drunk-driving laws.